1983
DOI: 10.1002/j.1551-8833.1983.tb05075.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the calcium carbonate saturation indexes

Abstract: Formulas for calculating six saturation indexes are derived. The indexes are expressed in terms of commonly measured characteristics of water quality. They are evaluated for their ability to determine whether a water is undersaturated, saturated, or oversaturated with respect to calcium carbonate (CaCO3) and to predict the water's capacity for CaCO3 deposition or dissolution. Important concepts that are often poorly understood are clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Langelier Saturation Index [8] [14], LSI of −1.4 was obtained by utilizing the parameter, signifying that the water is corrosive. Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Langelier Saturation Index [8] [14], LSI of −1.4 was obtained by utilizing the parameter, signifying that the water is corrosive. Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Caldwell Lawrence chart [6] [7] [8] has been widely utilized in practice to achieve the goal, which is complicated in the procedures of use; and also, restricted charts are only available so that it does not reflect diversified water quality characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…As Rossum and Merrill (1983) and Singley (1981) point out, these indices do not accurately predict the corrosiveness of water in all cases; however, in a nationwide study, Millette and others (1980) found that the Aggressive Index gave an adequate estimate of the aggressiveness (corrosiveness) of water. Sharpe and DeWalle (1985) report a good correlation between the corrosiveness of cistern water as predicted by the Ryznar Index and standing tap-water copper concentrations.…”
Section: Fe(oh)3+3h+ +Ementioning
confidence: 99%
“…The Aggressive Index has been described as a rough approximation of the widely used Langelier Saturation Index (Rossum and Merrill, 1983). Values of the Langelier Saturation Index are negative for water undersaturated with respect to calcium carbonate, zero for saturation, and positive for supersaturation.…”
Section: Fe(oh)3+3h+ +Ementioning
confidence: 99%
“…The corrosiveness of the tap water depends on chemical factors, such as pH, alkalinity, buffer intensity, dissolved oxygen and total dissolved solids (TDS), and physical properties, such as temperature, flow and velocity, as well as the nature of the pipe material [3][4][5]. In the water treatment process, pH, alkalinity and calcium hardness can be manipulated for the removal of color and corrosion control to prevent internal corrosion of a water distribution system [6,7].…”
Section: Introductionmentioning
confidence: 99%